(untitled) (Revista Brasileira de Linguística Antropológica, 2013)
Norman McQuown has recently published a synthesis of J. AldenMason’s classification of South American languages. 1 Although everyone will acknowledge the importance of the systematic work of both Mason and McQuown, one cannot help feeling that Taylor’s criticism concerning the West Indies, ‘the present classification... complicates and obscures the perspective unnecessarily’ 2, can be applied in part also to South America.